Appendicular schwannoma: Case report of a rare differential of a right iliac fossa mass - Kumar Deb, Pratap; Kumar Sahu, Subrata; Bhattacharyya, Samir; Behera, Tapas (Indian Journal of Case Reports, 2024)
Schwannomas are slow growing, mostly benign tumors arising from the Schwann cells of the nerve sheath. They usually arise from the nerves of the head-and-neck region. They are rare in the gastrointestinal tract. The stomach is the most common site for gastrointestinal schwannomas. Appendicular schwannomas are even a rarer entity that may present as a right iliac fossa mass. The final diagnosis is by histopathology and immunohistochemistry. Treatment is essentially surgical. Such entities may present as diagnostic dilemmas presenting as the not-so-common cause of iliac fossa mass and hence deserve reporting and discussion. We report our experience of treating a case of appendicular schwannoma in a 70-year-old lady with a short discussion on its characteristics and management.